Proteomic Markers of Non-functional Overreaching During the Race Across America (RAAM): A Case Study - Merritt, Edward K.; Nieman, David C.; Toone, Brian R.; Groen, Arnoud; Pugachev, Artyom (Frontiers in Physiology, 2019)
Previously, proteomics procedures identified blood proteins as potential overreaching and overtraining biomarkers, and a targeted proteomics panel of 21 proteins was developed. PURPOSE: To measure targeted protein changes in an ultraendurance cyclist competing in RAAM. METHODS: The athlete underwent testing 4-wks pre-RAAM and 4-d post-RAAM to determine body composition and aerobic capacity. During RAAM training distress score (TDS) and body mass were measured. Power output and heart rate (HR) were measured during cycling. Blood sampling for proteomic analysis occurred 4 wks, 24-h, and 2-h before the start, twice per day of RAAM, and after 1 and 4d recovery. RESULTS: The athlete completed the 4941-km race in 10.1 d at a speed of 24.5 km/h with 20 hours of sleep. TDS was very low, 1, pre-RAAM and increased to very high, 47, at the finish. Post-RAAM maximal aerobic capacity and HR were 6.3% and 5.7% lower (61.6 vs. 57.5 mL∙kg-1∙ min-1 & 192 bpm vs 181 bpm). Body composition did not change. The change in blood proteins was calculated using pre-race samples and samples from days 8, 9,and recovery day 1. The blood proteins with the largest increase were complement component C7 (359%), complement C4-B (231%), serum amyloid A-4 protein (210%), inter-alpha-trypsin inhibitor heavy chain H4 (191%), and alpha-1-antitrypsin (188%). CONCLUSION: The RAAM athlete exhibited non-functional overreaching symptoms including increased training distress and decreased work capacity. Proteomic analysis indicated large increases for immune-related proteins involved with complement activation and the acute phase response, which could be useful biomarkers for non-functional overreaching.